2017
DOI: 10.1016/j.ijscr.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary pulmonary meningiomas: 20-year follow-up findings for a first reported case confirming a benign biological nature

Abstract: HighlightsAn 84-year-old Japanese woman with a history of multiple primary meningiomas (PPMs) we first reported.Histologically confirmed for a right-sided slowly growing lung nodule for 20 years.Long-term follow-up CT scans reveal multiple lung nodules.Multiple PPMs are most effectively treated with surgical resection and follow-up examinations.The tumors prove to be benign by morphology with a relatively long, asymptomatic clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…The prognosis of benign PPM resection is good, with almost no recurrence or metastasis. There have been many reported cases with follow‐up longer than 20 years . However, there are also reports of malignant PPMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of benign PPM resection is good, with almost no recurrence or metastasis. There have been many reported cases with follow‐up longer than 20 years . However, there are also reports of malignant PPMs.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reported cases with follow-up longer than 20 years. 13 However, there are also reports of malignant PPMs. Prayson et al reported a rare, very aggressive case of PPM.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it is widely accepted that a wedge resection with tumor-free margins is sufficient for the treatment of benign PPM. The prognosis is reported to be excellent and extended resections are not required (3)(4)(5). In accordance with the literature, we performed wedge resection in the case.…”
mentioning
confidence: 58%
“…However, there are several reports on the occurrence of metastasis in benign meningiomas (WHO grade I). 17,18 A recent systematic review 19 of distant metastasis of meningiomas published in 2013 identified only 115 cases; 34% of them originated from benign meningiomas, while the remainder were atypical (21%) and malignant (40%) meningiomas, most often appearing almost five years after the first surgery.…”
Section: Discussionmentioning
confidence: 99%